2022
DOI: 10.1177/13506501221074801
|View full text |Cite
|
Sign up to set email alerts
|

Friction model of elastic-plastic line contact in mixed lubrication regime with non-Newtonian lubricant

Abstract: The friction characteristics of the lubricated rough surfaces are of great significance for the lubrication design of mechanical structures. To study the behaviour of friction coefficient in the rolling-sliding coexisting line contact rough surfaces under mixed lubrication regime, the Kogut-Etsion elastic-plastic model and the Carreau rheological model are utilized to describe the dry rough contact and the non-Newtonian characteristics of the lubricant film, respectively. A mixed lubrication model for predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Table 3 represents the parameters, namely, rolling speed ( U r ), skewness ( S sk ), kurtosis ( S ku ), material hardness ( H ) and pattern ratio ( γ ) and their minimum (min) to maximum (max) range, which are used as the input features in the MLP model. It should be noted that the min-to-max range of parameters as shown in Table 3 has been considered previously for the friction and wear analysis of non-conformal contacts (Ling et al , 2022; Taylor and Sherrington, 2022). It should also be noted that the contact load ( p max = 1.75 GPa) and RMS roughness ( S q = 0.3 µm) are kept constant during the generation of the input data set.…”
Section: Methodsmentioning
confidence: 99%
“…Table 3 represents the parameters, namely, rolling speed ( U r ), skewness ( S sk ), kurtosis ( S ku ), material hardness ( H ) and pattern ratio ( γ ) and their minimum (min) to maximum (max) range, which are used as the input features in the MLP model. It should be noted that the min-to-max range of parameters as shown in Table 3 has been considered previously for the friction and wear analysis of non-conformal contacts (Ling et al , 2022; Taylor and Sherrington, 2022). It should also be noted that the contact load ( p max = 1.75 GPa) and RMS roughness ( S q = 0.3 µm) are kept constant during the generation of the input data set.…”
Section: Methodsmentioning
confidence: 99%
“…research showed that the shear thinning behavior (pseudo plastic) of many lubricants (especially polymer-based lubricants) can be accurately characterized using the Carreau model [39,40]. So, in this work, the non-Newtonian characteristics of the lubricant are modelled by employing the Carreau equation [40]. The relationship between generalized viscosity η e of lubricant and shear strain rate (  g) is given in equation ( 9).…”
Section: Hydrodynamic Lubrication Modelmentioning
confidence: 99%
“…This strongly indicates that the surface roughness effect cannot be overlooked in elastohydrodynamic analysis of non-conformal contacts. Recently, Li et al [40] developed a line contact mixed-EHL model for predicting the traction coefficient considering non-Newtonian rheology of lubricant. They also showed the effect of surface roughness, speed, and lubricant viscosity on traction behavior.…”
Section: Introductionmentioning
confidence: 99%